The effect of transcutaneous electrical acupoint stimulation on postoperative awakening after general anaesthesia: a systematic review and meta-analysis - Si, Shangkun; Zhao, Xiaohu; Mu, Yuejun; Xu, Li; Wang, Fulei; Zhang, Dongbin; Su, Fan (Frontiers in Medicine, 2024)
The existing body of research concerning the impact of transcutaneous electrical acupoint stimulation (TEAS) on early postoperative recovery is marked by a lack of consensus. This meta-analysis, encompassing a systematic review of randomized controlled trials, seeks to critically assess the efficacy of TEAS in relation to awakening from general anaesthesia in the postoperative period. A comprehensive search was conducted across several reputable databases, including PubMed, Embase, the Cochrane Library, the China National Knowledge Infrastructure, the VIP Database, the Sinomed Database, and the WANFANG Medical Database. The search was not limited by date, extending from the inception of each database up to December 2023.The analysis encompassed twenty-nine studies involving a total of 2,125 patients.Participants in the TEAS group demonstrated a significantly shorter duration to achieve eye-opening (mean difference [MD], -3.16 minutes; 95% confidence interval [CI], -3.93 to -2.39), endotracheal extubation (MD, -4.28 minutes; 95% CI, -4.79 to -3.76), and discharge from the post-anaesthesia care unit (MD, -8.04 minutes; 95% CI, -9.48 to -6.61) when compared to the control group receiving no or sham stimulation. Additionally, the TEAS group exhibited markedly reduced mean arterial blood pressure (MD, -9.00 mmHg; 95% CI, -10.69 to -7.32), heart rate (MD, -7.62 beats per minute; 95% CI, -9.02 to -6.22), and plasma concentrations of epinephrine (standardised mean difference, -0.81; 95% CI, -1.04 to -0.58), norepinephrine (MD, -47.67 pg/mL; 95% CI, -62.88 to -32.46), and cortisol (MD, -110.92 nmol/L; 95% CI, -131.28 to -90.56) at the time of extubation. Furthermore, the incidence of adverse effects, including agitation and coughing, was considerably lower in the TEAS group relative to the control group (odds ratio, 0.30; 95% CI, 0.22 to 0.40).The findings of this study indicate that TEAS may hold promise in facilitating the return of consciousness, reducing the interval to awakening post-general anaesthesia, and enhancing the awakening process to be more tranquil and secure with a diminished likelihood of adverse events. However, caution must be exercised in interpreting these results due to the notable publication and geographical biases present among the studies under review. There is an imperative for further highquality, low-bias research to substantiate these observations.